Selection of natural fibre for pultruded hybrid synthetic/natural fibre reinforced polymer composites using analytical hierarchy process for structural applications - Balakrishnan, Thinesh Sharma; Sultan, Mohamed Thariq Hameed; Naveen, Jesuarockiam; Shahar, Farah Syazwani; Najeeb, Muhammad Imran; Md Shah, Ain Umaira; Khan, Tabrej; Sebaey, Tamer Ali (MDPI, 2022)
Application of synthetic fibres in composites has been raising environmental issues due to carbon emissions from the production site and reliability on non-renewable resources upon production. Hence, this research sets as a preliminary study to select suitable natural fibres to be hybridized with glass fibres for the development of sustainable and high-performance hybrid composites as potential alternative to conventional pultruded fibreglass composites in structural profile applications. In this study, analytical hierarchy process (AHP) was conducted to select the ideal natural fibre as reinforcement in the hybrid pultruded FRP composites suitable for structural applications. Hence, 13 natural fibre candidates were selected as alternatives and six criteria were chosen and analysed to select the best candidate for pultruded hybrid FRP. Criteria such as tensile strength, tensile modulus, density, cellulose content, elongation, and availability of fibres were assigned as the standard of selecting natural fibres for the application intended in this study. Among the 13 alternatives, kenaf was found to be the most suitable reinforcement for the application as it yielded the highest priority vector at 0.1. The results were then validated by carrying out sensitivity analysis to ensure kenaf is the most suitable material for the research.